Efektivitas Peningkatan Pelayanan Oleh Partisipasi Publik Dengan Pengaduan Sistem Layanan Aspirasi Pengaduan Online Rakyat (LAPOR) di Kota Malang - Eka Nur Aning Aisyah; Dinda Salwa Nabila; Michelle Alicia Sabrina; H Hayat (Universitas Warmadewa, 2024)
The People's Online Complaint Aspiration Service System (LAPOR) has emerged as a significant innovation in Indonesia, contributing to increased responsibility, accountability and openness in public services. One of the big cities in Indonesia, Malang City, has implemented this method as an effort to increase the efficiency of services provided to the community. This essay uses a combination of qualitative and quantitative research approaches. The number of complaints, response times, and resolution rates are all measured. It seeks to understand users' experiences and perceptions of the system through a qualitative research approach. Collect information regarding the number, nature and location of complaints as well as the time and place of response from the Malang city LAPOR database. Data shows that several regional apparatuses in Malang City have a high response rate to public complaints, an average of 93.67% for SAMBAT WEB and 84.85% for SAMBAT SMS. This shows that the online complaint system has succeeded in meeting the public's expectations and needs for fast and effective responses to their complaints. In the period January to December 2020, the Malang City Communications and Information Service received a total of 869 complaints via the SAMBAT WEB and SAMBAT SMS applications. The five regional agencies with the most complaints are the Transportation Service (Dishub), Population and Civil Registration Service (Disdukcapil), Civil Service Police Unit.